1985
DOI: 10.1002/j.1551-8833.1985.tb05521.x
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate Parameters for Monitoring Organic Matter and THM Precursors

Abstract: IJV absorbance at 254 nm is an excellent surrogate parameter for estimating the raw water concentrations of organic carbon (NPTOC-nonpurgeable total organic carbon) and THM precursors (TTHMFP-total trihalomethane formation potential) in the Grasse River (highly colored water) and the Glenmore Reservoir (protected, upland source). The raw water surrogate equations developed from the Grasse River data were tested successfully on other waters. Direct filtration pilot-plant data demonstrated that IJV can be used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
185
1
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(203 citation statements)
references
References 23 publications
15
185
1
2
Order By: Relevance
“…This is consistent with the findings of other researchers (e.g. [5,6,17,19]). Some investigators have shown that hydrophobic carbon is more readily removed by certain treatment processes, e.g.…”
Section: Removal Of Dbp Precursors With Miexsupporting
confidence: 94%
See 2 more Smart Citations
“…This is consistent with the findings of other researchers (e.g. [5,6,17,19]). Some investigators have shown that hydrophobic carbon is more readily removed by certain treatment processes, e.g.…”
Section: Removal Of Dbp Precursors With Miexsupporting
confidence: 94%
“…This is consistent with the published literature which indicates that UV254 is a good surrogate for THM formation potential (e.g. [17,18]). Similar trends were observed for THM and HAA formation potential in the other waters, although not all graphs showed as strong a trend as Figs.…”
Section: Removal Of Dbp Precursors With Miexsupporting
confidence: 93%
See 1 more Smart Citation
“…The NOM is quite complicated in nature since it contains a variety of chemical components with a large distribution of molecular weights. The source waters with a high SUVA are generally enriched in hydrophobic and high molecular weight NOM, such as ionization of carboxyl groups and humic substances [35,36]. The ozone can cleave the unsaturated bonds in the aromatic moieties that are found in humic materials, which makes the organic molecules smaller, more oxidized, and more biodegradable; however, it cannot mineralize the organic carbon into inorganic carbon.…”
Section: Performance Of the Nom Removal By Ozonementioning
confidence: 99%
“…3b shows that not only the hydrophobic acid but also the hydrophilic have higher THMFP. The result shows that if the organic is hydrophilic and low molecular weight organic pollution is very likely to have higher THMFP, thus it could pose health issue of the formation of DBPs in disinfection process with Cl 2 [11,12].…”
Section: Thmfp Of Nommentioning
confidence: 99%